Evaluation of cadmium tolerance and remediated efficacy of wild and mutated Enterobacter species isolated from potassium nitrate (KNO₃) processing unit contaminated soil. (January 2023) - Lu, Haiying; Xia, Changlei; Chinnathambi, Arunachalam; Nasif, Omaima; Narayanan, Mathiyazhagan; Shanmugam, Sabarathinam; Lan Chi, Nguyen Thuy; Pugazhendhi, Arivalagan; On-uma, Ruangwong; Jutamas, Kumchai; Anupong, Wongchai
Abstract: The purpose of this study was to find the most cadmium (Cd 2+ ) tolerant and remediated bacteria isolate from KNO3 processing unit contaminated soil. One isolate out of 19 isolates possessed excellent Cd 2+ tolerance than others, which was recognized as Enterobacter hormaechei SFC3 through molecular characterization (16S rRNA sequencing). The identified E. hormaechei SFC3 contained 55% and 45% of GC and AT content, respectively. The wild and acridine orange mutated E. hormaechei SFC3 exhibited excellent resistance to Cd 2+ up to the concentration of 1500 μg mL −1 . Furthermore, the wild E. hormaechei SFC3 and mutated E. hormaechei SFC3 showed 82.47% and 90.21% of Cd 2+ remediation on 6th days of treatment respectively. Similarly, the Cd 2+ tolerant wild and mutated E. hormaechei SFC3 showed considerable resistance to all the tested antibiotics. The findings indicate that E. hormaechei SFC3 isolated from KNO₃ processing unit contaminated soil is a promising candidate for microbial remediation of Cd 2+ contamination. Graphical abstract: Image 1 Highlights: First report on enumerating Cd tolerant bacteria from firework industry polluted soil. Enterobacter hormaechei SFC3 was found as predominant Cd tolerant bacteria. Acridine orange (500 μg mL −1 ) mutated E. hormaechei SFC3 showed excellent tolerance. Wild & acridine orange mutated E. hormaechei SFC3 showed 82 & 90% of Cd 2+ remediation. Both strain showed considerable resistance to various tested antibiotics.